Optimization of Green and Hardness Protection Technology of Frozen Green Pepper - Changting DU; Feng HUANG; Xuhua CHEN; Chunhui ZHANG (Shipin gongye ke-ji, 2024)
To diminish the browning and tissue softening issues of green pepper dishes in the freezing/thawing processes, salt, trehalose and calcium chloride were used to treat thawed green peppers, and the hardness, drip loss rate, chlorophyll content, sensory evaluation and microstructure of thawed green peppers were measured to verify the effect of process green protection and hard preservation. A single factor experiment was used to screen the optimum range of each factor and response surface methodology was chosen to obtain the optimum process parameter combination. Results showed that the optimum process for protecting green and hardness properties of green pepper was as follows: Blanching green pepper at 100 ℃ for 5 s, the mass fraction of salt in the blanching solution was 0.50%, immersed in cold water for 15 min, the mass fraction of trehalose was 0.51%, and the mass fraction of calcium chloride was 0.25%. Under this process condition, compared with the control group, the color difference of green pepper in the treatment group was reduced by 3.98, the hardness was increased by 20.37%, the juice loss rate was decreased by 40.29%, the chlorophyll content and sensory score were increased by 102.70% and 88%, respectively. Through the scanning electron microscopy, it was found that the treated green pepper cell wall was more complete and maintained a better cell structure. This process can effectively maintain the color and taste of green pepper after thawing, which can provide data support for the research of green and hardness preservation technology of frozen green pepper prefabricated vegetables.